Information systems auditing and assurance - Hall, James A., 1944- (Cincinnati, Ohio : South-Western College, 2000)
This book is about: Auditing, Assurance, and Internal control; Computer operations; Data management systems; Electronic commerce systems; ...
Keywords: Data processing; Auditing; Electronic data processing; Electronic data processing -- Auditing